A modern colonial vision of the Andean world. Criollo and Indians in «Amor indígena» by Ventura García Calderón - López Maguiña, Santiago (2019)
This text is part of a series of analyzes inspired by French semiotics. This is a discipline that demands rigor, although at the same time it does not disdain intuition and exploration beyond its borders. It attempts to systematize the representation of the most pregnant stereotypes of Peruvian culture and literature. It seeks to build schemes and as far as possible explanatory models. To begin the project, a story by Ventura García Calderón has been chosen that offers a colonial Creole look of the indigenous. It is a pejorative look, as well as an affirmation of the values of the dominant Peruvian nobleman class, during the first decades of the last century.